Impact of High-Temperature, High-Pressure Synthesis Conditions on the Formation of the Grain Structure and Strength Properties of Intermetallic Ni[3]Al - Ovcharenko V. E. Vladimir Efimovich; Ivanov K. V.; Boyangin E. N.; Krylova T. A.; Pshenichnikov A. P. (2018, 2018)
Title screen